PARTNERSHIP MODEL AS EMPOWERMENT BETWEEN VOCATIONAL SCHOOLS AND BUSINESS WORLD/INDUSTRIAL WORLD - Widodo Widodo; Dianna Ratnawati; K Isma Ismara; Wagiran Wagiran (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to find a model of vocational partnership development with Business World (BW)/Industrial World (IW) that is suitable to be applied in Indonesia. The model that bridges the partnership relationship between vocational schools and BW/IW is developed based on factual conditions in the field, existing theoretical models and focuses on the concept of link and match between the relevant institutions. Vocational school discussion forums and BW/IW are held as a means of brainstorming between stakeholders. Data collection through open questionnaires is used to hear directly the opinions of stakeholders regarding the expected partnership model. The basis of the model which is used as the basis of the foundation is industrial training, Dual System Education (DSE), Teaching Factory and Work Based Learning. The Vocational School in general provides information on cooperation undertaken which requires open recruitment standards to enter the BW/IW which are clear, legal umbrella regulations from the government. The following models are produced by Industrial cooperation with Vocational Schools, the cooperation model includes three aspects: 1) the needs in BW/IW, 2) the regional ecosystems produced by BW/IW with vocational schools, and 3) the needs of the vocational schools learning process.